Management Accounting Techniques on Rationalize Decisions in the Nepalese Listed Manufacturing Companies - Dahal, Rewan Kumar; Bhattarai, Ganesh; Karki, Dipendra (Researcher: A Research Journal of Culture and Society, 2020)
The objective of this study was to examine how much the Nepalese listed manufacturing companies are utilizing management accounting techniques to rationalize decisions. It followed a descriptive research design and employed a survey questionnaire instrument to collect data. The population of this study comprised all the listed manufacturing companies on the Nepal Stock Exchange and their employees. Targeted respondents were those representatives of the sample companies who worked in the accounting department or/and at the managerial level. By using a random sampling technique, a sum of 408 respondents had partaken in the survey and 385 responses were properly filled up for further analysis. The survey questionnaire had three questions relating to general and demographic information, 28 questions relating to management accounting techniques, and five questions relating to the effect of the study variables on rationalizing decisions. Collected data were analyzed with the help of a statistical package for the social sciences software. Each of the 28 management accounting techniques was classified into nine groups and identified that most of the techniques except financial performance measurement techniques (having with cash flow analysis, ratio analysis, absorption/variable costing, transfer pricing) had no significant relation with rationalizing decisions in the Nepalese manufacturing companies. So, this study would assist to pay attention to the concerned personnel towards the use of management accounting techniques on rationalize decisions.